Zakat Surplus Funds Management - Saad, Ram Al Jaffri; Sawandi, Norfaiezah; Mohammad, Rahayu (International Journal of Economics and Financial Issues, 2016)
The success of zakat institutions in managing the affairs of the zakat fund cannot be denied. Zakat collection has been increased substantially every year. However, one issue that is still being debated is the issue of zakat fund surplus. The purpose of this paper is to discuss two key points. First, to identify whether zakat fund surplus exists or not at the time of Prophet Muhammad (PBUH) and the Caliphs after Prophet Muhammad (PBUH). Second, to discuss the developments in the management of zakat fund surplus. The content analysis method was employed to achieve the objectives. Results show that there is a surplus of zakat funds reported during the reign of Caliph Umar Abdul Aziz. The study also found that surplus of zakat funds can be managed by investing the zakat fund surplus for the benefit of the zakat recipients (asnaf). Keywords: Zakat Collection, Zakat Distribution, Fund Surplus, Management JEL Classification: M40